Estimations of the energy quasi-integral of the restricted three-body problem - Chorny, G.F. (Кинематика и физика небесных тел, 2005)
We consider the restricted three-body problem for a dust particle in the vicinity of a spherical cometary nucleus in an eccentric orbit about the Sun. The differential equations of the particle’s spatial motion are integrated both analytically and numerically to obtain and estimate the energy quasi-integral.